UPAH DAN LINGKUNGAN KERJA KAITANNYA TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Harti, ; Siti Anisah, (Pendidikan Ekonomi, 2011)
The study was intended to examine the effect of wage and working environment on the employees work productivity in Written Batik Gedog firm, UD Budi Karya Kerek Tuban. The study was quantitative research. The data were collected with payroll, questionnaire, and production list. The data were then analyzed with multiple linier regression.The findings showed that wage and working environment affected significantly the work productivity of employees. The effect of wage and working environment on the work productivity reached by 76.8 %, while other variables affected 23.2 % of the work productivity. Wage had dominant influence on the productivity.